Nano and Micro Diamond Formation in Nature Ultrafine Carbon Particles on Earth and Space - Simakov, Sergei; Scribano, Vittorio; Melnik, Nikolai; Pechnikov, Victor; Drozdova, Irina; Vyalov, Vladimir; Novikov, Mikhail (Cham : Springer International Publishing : Imprint: Springer, 2023)
In this book, readers will gain a deep understanding of the distinct characteristics and intricate formation mechanisms behind each type of diamond. A standout feature of this book is its in-depth exploration of nanodiamonds, shedding light on their unique formation processes. The narrative is thoughtfully organized, covering four main categories of natural diamonds and their related formation processes: 1)Interstellar nanodiamond particles; 2) Nano- and microcrustal diamonds associated with coals, sediments, and metamorphic rocks; 3) Nanodiamonds and microdiamonds associated with secondary alterations of mafic and ultramafic rocks mainly in the oceanic lithosphere; 4) Mantle-derived diamonds associated with kimberlites and their xenoliths, such as peridotites and eclogites. With clarity and precision, this book caters to both researchers and students in the fields of mineralogy and mineral formation. This book serves as an invaluable resource, offering an all-encompassing perspective on diamond formation, appealing to those curious minds eager to delve into the captivating realm of these precious gems.
Chapter 1. Introduction -- Chapter 2. Diamond thermodynamic stability: The paradox of the crystal size -- Chapter 3. Experimental data on nanocarbon formation at low P-T conditions -- Chapter 4. Diamond formation in the Oceanic Lithosphere -- Chapter 5. Nanocarbon and microdiamond formation in the lithogenesis and metamorphic processes -- Chapter 6. Diamonds in kimberlites and their xenoliths: A reappraisal -- Chapter 7. Conclusions.
Keywords: Geochemistry; Mineralogy; Nanochemistry; Biogeography; Geochemistry; Mineralogy; Nanochemistry; Biogeosciences